Phytochemical constituents and antimicrobial activity of the ethanol and chloroform crude leaf extracts of Spathiphyllum cannifolium (Dryand. ex Sims) Schott - Arunachalam Dhayalan; Daniel E Gracilla; Renato A Dela Peña Jr; Marilyn T Malison; Christian R Pangilinan (Wolters Kluwer Medknow Publications, 2018)
Context: The study investigated the medicinal properties of Spathiphyllum cannifolium (Dryand. ex Sims) Schott as a possible source of antimicrobial compounds. Materials and Methods: The phytochemical constituents were screened using qualitative methods and the antibacterial and antifungal activities were determined using agar well diffusion method. Statistical Analysis: One-way analysis of variance and Fisher's least significant difference test were used. Results: The phytochemical screening showed the presence of sterols, flavonoids, alkaloids, saponins, glycosides, and tannins in both ethanol and chloroform leaf extracts, but triterpenes were detected only in the ethanol leaf extract. The antimicrobial assay revealed that the chloroform leaf extract inhibited Candida albicans, Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Pseudomonas aeruginosa, whereas the ethanol leaf extract inhibited E. coli, S. aureus, and B. subtilis only. The ethanol and chloroform leaf extracts exhibited the highest zone of inhibition against B. subtilis. The antifungal assay showed that both the leaf extracts have no bioactivity against Aspergillus niger and C. albicans. Conclusions: Results suggest that chloroform is the better solvent for the extraction of antimicrobial compounds against the test organisms used in this study. Findings of this research will add new knowledge in advancing drug discovery and development in the Philippines.